Dropping the non-core subjects from undergraduate final professional examination: How it would impact the results - Thomas, Puthiaparampil T.; Nariman, Singmamae; Shazrina, Ahmad Razali; Sabrina, Lukas; Chai, Chee Shee; Rahman, Md Mizanur (Malaysian Medical Association, 2022)
Introduction: Observing the dearth of distinctions in the two decades of final professional medical examinations (FPE) caused concern. Multiple True False (MTF) tests with penalty scoring pulling down the scores was considered one reason. Another possible reason was having too many subjects covered in the MTF and Best Answer Question (BAQ) papers. This study aimed to explore the impact of dropping the non-core subjects with minimal inputs from MTF and BAQ papers and the students’ views in this regard. Materials and Methods: We examined the students’ performance in the core and non-core subjects in MTF and BAQ papers and the impact of dropping the non-core subjects’ contribution to the students’ scores of the recent four final professional examinations. We also surveyed the opinions of the students, who took the FPE in the year 2000. Results: The failure rates were significantly higher in noncore than core subjects (p < 0.001) except in one MTF paper. The mean scores were significantly lower in non-core than core subjects in all the four FPEs (p < 0.05) except in one MTF paper. Dropping the non-core subject items from MTF and BAQ showed an improvement in the scores of MTF, theory total, and most grand totals resulting in two more students reaching distinction status. A mere 3.8% of the students could thoroughly revise the non-core subjects before the FPE. Two-fifth of them believed that non-core subjects had a significant impact on theory performance. Only 31.5% favoured dropping the non-core subjects, and an equal number preferred a status quo, while the rest suggested a reduction in their weightage. Conclusion: Most of the students considered the non-core subjects important in their career. However, very few of them could revise these subjects for the professional examination. The study demonstrated that dropping the non-core subjects from MTF and BAQ improved the students’ final scores and helped more students to attain distinction status.